Quality Control on Bogo Helmet Coating Process Using the Six Sigma Method, Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA) - Paulina Retno Anjani Sugito; Elly Wuryaningtyas Yunitasari; Syamsul Ma’arif (Jurnal Engine: Energi, Manufaktur, dan Material, 2023)
Hanesda Assembling Helmet is a private company engaged in the assembly of bogo helmets. One of the serious problems faced by this company is that the defective products produced in the production process reach 4% of the tolerance limit set by the company, which is 1.5%. The purpose of this research is to control the quality of the coating process which has a lot of product defects. The method used in this study is the Six Sigma method with the stages of DMAIC. The method used to analyze the causes of failure is the FTA method and the method used to determine the weighting in prioritizing the repair design is the FMEA method. The results of the research using the Six Sigma method are obtained DPMO values of 19,931 with a Sigma level of 3.57. Types of defects that have the highest RPN are streak defects, flex defects, uneven paint defects and paint runs defects with an RPN value of 112. High RPN value will be prioritized for improvement plans.